2017
DOI: 10.5603/gp.a2017.0059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hematologic system as a marker of subclinical inflammation in hyperemesis gravidarum: a case control study

Abstract: Objectives: Current evidence suggests that subclinical inflammation plays a significant role in the development of hyperemesis gravidarum (HEG). Simple hematological markers, such as mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), have been shown to reflect inflammatory burden and disease activity in several disorders. This study aimed to determine the diagnostic value of these hematological parameters for HEG. Material and methods:A total of 54 HEG pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…[161718] Several studies evaluating the significance of inflammation markers in HEG have been presented. [1213] Although the relationship between HEG and inflammation markers has been investigated previously, our study is unique due to its inclusion of the relationship between inflammation markers and ketonuria. [12] The results pertaining to ketonuria from this study may lead to prospective randomized trials of ketonuria in patients with HEG and provide objective discharge criteria, which are missing in the literature and clinical practice for HEG patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[161718] Several studies evaluating the significance of inflammation markers in HEG have been presented. [1213] Although the relationship between HEG and inflammation markers has been investigated previously, our study is unique due to its inclusion of the relationship between inflammation markers and ketonuria. [12] The results pertaining to ketonuria from this study may lead to prospective randomized trials of ketonuria in patients with HEG and provide objective discharge criteria, which are missing in the literature and clinical practice for HEG patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2324] Beyazit et al . [12] found that PDW and MPV did not differ significantly between HEG patients and controls. Tayfur et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDW was tested also in the evaluation of hyperemesis gravidarum (HEG), a medical condition of intractable vomiting during pregnancy affecting approximately 0.3 - 2% of all pregnancies ( 36 ). The study was performed in 54 HEG patients and 58 age- and gestational-age-matched controls, but no statistically significantly differences with RDW-CV were detected (12.1% ± 1.4 vs. 12.6% ± 1.7, P > 0.05)…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the worst aspect of diabetes is the systemic inflammation and oxidative stress and they are almost accused of being the real reasons underlying many complications of diabetes [14] [15] [16]. MPV is now well known as a predictor of inflammation and has been shown in many cases as a marker of inflammation [17] [18] [19]. In our previous research, we have shown that we can use MPV in the diagnosis of uveitis and venous thrombosis in patients with Behçet's syndrome [20] [21].…”
Section: Introductionmentioning
confidence: 99%